Water erosion prediction using Revised Universal Soil Loss Equation and GIS: A case study of Gorganrud Basin - S. Abedian; A. Salmanmahiny (Environmental Resources Research, 2018)
Soil erosion and sedimentation processes can be considered as serious eco-environmentalproblems. This study aimed to estimate the basin-wide erosion using the Revised UniversalSoil Loss Equation (RUSLE). The soil erosion parameters included rainfall erosivity map generated from the rainfall data, soil erodibility extracted from the soil map, land cover andmanagement map produced from supervised classification of Landsat ETM+ data, and aDigital Elevation Model (DEM) to generate the slope length and steepness factor (LS)maps. Support practice map was assumed as 1 as there were no significant conservationpractices. Then, the six thematic layers were integrated based on RUSLE model in GISenvironment, and the spatial distribution of soil loss in the Gorganrud Basin was achieved.The distribution of erosion risk was 42.5% for low, 30.33% for moderate, and 27.17% forsevere classes. The highest amount of erosion occurred in the northwest to northeast andeastern regions with lithological units including loess, young terraces and alluvial depositsand agricultural use despite the fact that LS factors in these areas were less than 10. In thecentral and southern parts of the basin, in spite of the high values of LS factor (15–55),these areas depicted low to moderate erosion potential. This is supposed to be due to thedense forest coverage in the region that decreases the energy of rain droplets. The soilerosion risk map can be used for rapid assessment of the effects of environmental changesand watershed management interventions.